Managerial and Technical Inefficiencies of Foreign and Domestic Banks in Turkey During the 2008 Global Crisis - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2013)
This study analyses the differences between the group efficiency of foreign and domestic banks in Turkey from 2007 to 2010. The efficiencies of bank groups are compared after managerial inefficiencies are eliminated. In the process, the underlying factors of group efficiencies are identified. The results reveal that bank efficiencies are highly affected by their association with the bank groups. The efficiencies of foreign banks are higher than those of domestic banks both before and after managerial inefficiencies are eliminated. Surprisingly, foreign banks are found to have been highly or fully efficient during the global financial crisis, once the managerial inefficiencies are removed.
Keywords: bank efficiency; bootstrap; DEA; foreign ownership; group efficiency; Turkey; NONPARAMETRIC FRONTIER MODELS; DATA ENVELOPMENT ANALYSIS; DECISION-MAKING UNITS; TRANSITION ECONOMIES; EFFICIENCY SCORES; SCALE; OWNERSHIP; SECTOR; COST